The Influence of Retail Investor Activity and Sentiment on Social Media on Stock Market Dynamics in Bali - I Gusti Ngurah Agung Dananjaya; Made Aristia Prayudi; I Gd Nandra Hary Wiguna (E-Jurnal Akuntansi, 2025)
The growing participation of retail investors in social media communities has created a pressing need to understand how their activities and sentiments influence stock market dynamics. This study aims to examine the effect of investor activity and sentiment on social media on the trading volume and price volatility of small-cap stocks. A quantitative approach was adopted by surveying 200 respondents who are active in online stock communities. The data were analyzed using multiple linear regression. The results indicate that both investor activity and sentiment are positively associated with trading volume and price volatility. The regression models explain more than half of the variation in the two dependent variables. The study concludes that social media plays a significant role as a space that shapes the behavior and investment decisions of retail investors in the digital stock market.